PENGARUH MODEL LEARNING CYCLE 5E TERHADAP PEMAHAMAN KONSEP SISWA SMP NEGERI 2 GALESONG SELATAN PADA MATERI SUHU DAN KALOR - Bahrur Rahman Hasba; Hasrianti; Faradilah, Nurul; Sidra, Nuridilah; Iffah, A. Nur; Amelia, Andi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of the Learning Cycle 5E model on students' conceptual understanding of temperature and heat at SMP Negeri 2 Galesong Selatan. The research employed a quantitative approach using a quasi-experimental design with a nonequivalent control group design. The population consisted of all seventh-grade students of SMP Negeri 2 Galesong Selatan in the academic year 2025/2026. The sample was selected through purposive sampling, involving class VII-A as the experimental group and class VII-B as the control group. Data were collected through pretest and posttest instruments consisting of conceptual understanding questions on temperature and heat. Data analysis included descriptive statistics and inferential statistics using an independent sample t-test. The results showed that the average posttest score of the experimental class was higher than that of the control class. The N-Gain score in the experimental class reached 0.69 (moderate category), while the control class obtained 0.42 (moderate category). The t-test results indicated a significance value of 0.000 < 0.05, meaning that there was a significant effect of the Learning Cycle 5E model on students’ conceptual understanding. Therefore, the Learning Cycle 5E model can be recommended as an effective learning model for improving conceptual understanding in science learning, especially on temperature and heat topics.